Can socioeconomic factors influence the establishment of information mutation in local medical systems? A case study on the use of plant complexes - Pereira, Mateus Rocha da Silva; Dantas, Janilo Ítalo Melo; do Nascimento, André Luiz Borba; Silva, Taline Cristina (Ethnobiology and Conservation, 2021)
Information mutations are unintended changes in information that can lead to the establishment of poorly adapted cultural traits in local medical systems. The use of plant mixtures in local medical systems, such as “bottles and lickers” could it be an important model to understand this phenomena, since the variability of information associated an only one plant mixture is high and may lead to an higher occurrence of error in the social transmition. In this study, we sought to investigate whether the socioeconomic variables: gender, age, and education influences the amount of information mutations on the knowledge of plant mixtures. Data collection followed the ethical parameters for research with human beings and consisted of two different applications of semi-structured interviews to access and analyze the Information Unit (IU) in regards to the passivity of information mutation between the individual learner and the individual giving information. We obtained 141 types of plant mixtures mentioned in the study. When analyzing our variables, age and education influenced the number of mutations (p